Cultural adaptation and content validity of a Chinese translation of the 'Person-Centered Primary Care Measure': findings from cognitive debriefing. Issue 4 (22nd September 2020) - Tse, Emily Tsui Yee; Lam, Cindy Lo Kuen; Wong, Carlos King Ho; Chin, Weng Yee; Etz, Rebecca S; Zyzanski, Stephen J; Stange, Kurt C
Abstract : Objectives: To develop an equivalent Chinese translation of the Person-Centered Primary Care Measure (PCPCM) and to establish its cultural adaptability and content validity through cognitive debriefing. Design: The original English PCPCM was first translated into Chinese by double forward-translation by professional translators. The reconciliated Chinese version was then doubly back-translated into English by two other professional translators blinded to the forward-translation. On affirmation on its linguistic equivalence with the developers of the original English PCPCM, the reconciliated Chinese PCPCM was sent for cognitive debriefing with 20 Chinese-speaking primary care subjects by a trained interviewer using structured probing questions to collect their opinions on the clarity, comprehensibility and relevance of each item and response option in the Measure. Setting: Subjects were invited from a primary care clinic in Hong Kong to undergo the cognitive debriefing interviews. The interviews were divided into four groups chronologically to allow revision of the items to be made in between. Participants: Ten males and 10 females above the age of 18 completed the cognitive interviews. They were all Cantonese-speaking Chinese recruited by convenience sampling. Subjects with cognitive impairment, could not read Chinese, too old or too sick to complete the interviews were excluded from the study. Results: An average of 3.3 min (range 3–4 min) was required for the subjects to self-complete the Measure. All items were generally perceived to be easily understood and relevant. Modifications were made to items with the content validity index (CVI) on clarity or understanding <0.8 in each round of the interviews or if a majority of the subjects suggested rewording. Revisions were made to two items in the Chinese PCPCM throughout the whole cognitive debriefing process before the final version was confirmed. The average CVI on clarity of the Chinese PCPCM items ranged from 0.75 to 1. The average CVI on understanding ranged from 0.7 to 1. The average CVI on relevance ranged from 0.55 to 1. Conclusions: The content validity of the PCPCM was ascertained in terms of its clarity, understandability and relevance to allow further testing of its psychometric properties in a larger Chinese population.